Array of Graphene Solar Cells on 100 mm Silicon Wafers for Power Systems - Syed M. Rahman; Md R. Kabir; Tamzeed B. Amin; James M. Mangum; Ashaduzzaman; Paul M. Thibado (Energies)
High electrical conductivity and optical transparency make graphene a suitable candidate for photovoltaic-based power systems. In this study, we present the design and fabrication of an array of graphene-based Schottky junction solar cells. Using mainstream semiconductor manufacturing methods, we produced 96 solar cells from a single 100 mm diameter silicon wafer that was precoated with an oxide layer. The fabrication process involves removing the oxide layer over a select region, depositing metal contacts on both the oxide and bare silicon regions, and transferring large-area graphene onto the exposed silicon to create the photovoltaic interface. A single solar cell can provide up to 160 μA of short-circuit current and up to 0.42 V of open-circuit voltage. A series of solar cells are wired to recharge a 3 V battery intermittently, while the battery continuously powers a device. The solar cells and rechargeable battery together form a power system for any 3-volt low-power application.